Measurement technique in radio frequency interference (RFI) study for radio astronomy purposes = [Teknik pengukuran dalam kajian gangguan interferen radio (RFI) bagi tujuan astronomi radio] - Umar, R.; Sabri, N.H.; Ibrahim, Z.A.; Abidin, Z.Z.; Muhamad, A. (Malaysian Society of Analytical Sciences, 2015)
In this paper, we will review our method in making measurements of radio frequency interference (RFI) in order to investigate the sereneness of interference in selected radio interference in Malaysia and Thailand. The selected site are University of Malaya (UM), Universiti Pendidikan Sultan Idris (UPSI), Ubon (UB) and Chiang Mai (CM). The major RFI affecting radio astronomical windows below 1 GHz are electronic equipment system specifically radio navigation between 73.1 MHz and 75.2 MHz, radio broadcasting (151 MHz, 151.8 MHz and 152 MHz), aeronautical navigation (245.5 MHz, 248.7 MHz and 249 MHz and also fixed mobile at 605 MHz, 608.3 MHz, 612.2 MHz, 613.3 MHz. It is obviously showed that all sites within this region are free from interference between 320MHz and 330 MHz and is the best specific region to be considered for solar burst monitoring. We also investigate the effect of RFI on discovery of solar burst.